The Subjective Well-Being of Children in Residential Care: Has It Changed in Recent Years? - Carme Montserrat; Joan Llosada-Gistau; Marta Garcia-Molsosa; Ferran Casas (Social Sciences, 2022)
The subjective well-being of children in residential care is a relevant issue given the practical implications for improving the lives of these children who live in contexts of vulnerability. The question addressed in this respect was: “How does this well-being change over the years”? Thus, the aim of this study was to compare the subjective well-being displayed by adolescents aged 11–14 in residential care in Catalonia (north-eastern Spain) in 2014 to that displayed by adolescents in residential care in 2020. To this end, 572 responses to a questionnaire adapted from the Children’s Worlds project (364 from 2014 and 208 from 2020) were analysed with respect to the life satisfaction items. In both 2014 and 2020, the questionnaires had the same wording, and data were disaggregated by gender. No significant differences in means were observed between most of the life satisfaction items in 2014 and 2020, with the exception of satisfaction with friends and classmates and the area where you live, with lower means for these items in 2020. There is a discussion of the possible influence of COVID-19 on these results, while the overall stability of these children’s subjective well-being over the years is highlighted.